Evaluation Report on Second Year's Working of Community Projects Volume II - Planning Commission (Planning Commission, 1955)
Although work was initiated simultaneously in all the three blocks in October 1952, even with the lapse of two years, intensity of work differs considerably from one block to another. Whereas almost all the villages in block I have been covered by some activity or the other, in the other two blocks coverage has been poor. For instance fertilizer loans were issued in 75 per cent, of the villages in block I, while in the other two blocks these were issued in 15 per cent, and 9 per cent, of the villages respectively. As regards works programmes such as drinking water wells, schools buildings, Communications etc., the coverage has been 37 per cent of villages in block I. 11 per cent, in block II and 15 per cent, in block III. Greater tempo of work in block I is the result of concentration of efforts by the project staff. Shortage of VLW’s in the other two blocks during the first year, and the fact that only one APO was in charge of the two blocks, which made supervision of village workers difficult, were the other reasons for slow progress in these blocks. Another factor is the inadequacy of funds considering the population to be reached (7-5 lakhs). It is feared that even after the close of the project period many villages would remain untouched by development activities. The villagers are conscious of this unevenness of work and this results in ill feelings towards the project.
Evaluation Report
Government of India